2-D to 3-D conversion of WO3 nanostructures using structure directing agent for enhanced NO2 gas sensing performance - Beknalkar, S. A.; Patil, V. L.; Harale, N. S.; Suryawanshi, M. P.; Patil, A. P.; Patil, V. B.; Kim, J. H.; Patil, P. S. (Sensors and Actuators A-Physical, 2020)
An exotic 3-D tungsten oxide (WO3) microflower was synthesized via low-cost and environmental-friendly hydrothermal strategy. The effect of structure-directing agent on the formation of 3-D microflowers from a 2-D nanosheets of WO3 and its gas sensing behavior are investigated. The assynthesized WO3 powder was used in morphological, structural and phase studies by X-ray diffraction (XRD), scanning electron microscopy (SEM), FT-Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The WO3 samples were found to be polycrystalline with monoclinic crystal structure. The SEM micrographs revealed the formation of 3-D microflowers made up of two-dimensional (2-D) multi-directional dendritic nanoplates. The potassium hydroxide (KOH) acts as a structure-directing agent in the formation of 3-D microflowers of WO3 sample. To further understand the formation of 3-D microflowers of WO3 sample, concentration-dependent experiments were carried out by varying KOH concentration and the formation mechanism was investigated. The synthesized WO3 microstructures were subjected to detailed gas sensing tests for different gases at an optimized temperature. A selective, sensitive gas response was obtained for WO3 gas sensor. The lower detection limit is about 1 ppm at 150 degrees C working temperature for an optimized WO3 gas sensor. The gas sensing results indicate that the 3-D microflower-like WO3 nanostructures are highly promising for applications as gas sensors. (C) 2020 Published by Elsevier B.V.
Keywords: Microflowers; NO2 detection; WO3

Bioinspired synthesis of multifunctional silver nanoparticles for enhanced antimicrobial and catalytic applications with tailored SPR properties - Parit, S. B.; Karade, V. C.; Patil, R. B.; Pawar, V. N.; Dhavale, R. P.; Tawre, M.; Pardesi, K.; Jadhav, U. U.; Dawkar, V. V.; Tanpure, R. S.; Kim, J. H.; Jadhav, J. P.; et al. (Materials Today Chemistry, 2020)
In the developing nanotechnology world, numerous attempts have been made to prepare the nobel metallic nanoparticles (NPs), which can improve their applicability in diverse fields. In the present work, the biosynthesis of silver (Ag) NPs has been successfully achieved through the medicinal plant extract (PE) of G. resinifera and effectively used for the catalytic and antibacterial applications. The size dependant tuneable surface plasmon resonance (SPR) properties attained through altering precursor concentrations. The X-ray and selected area diffraction pattern for Ag NPs revealed the high crystalline nature of pure Ag NPs with dominant (111) phase. The high-resolution TEM images show the nonspherical shape of NPs shifting from spherical, hexagonal to triangular, with wide particle size distribution ranging from 13 to 44 nm. Accordingly, the dual-band SPR spectrum is situated in the UV-Vis spectra validating the non-spherical shape of Ag NPs. The functional group present on the Ag NPs surface was analysed by FT-IR confirms the capping and reducing ability of methanolic PE G. resinifera. Further, the mechanism of antimicrobial activity studied using electron microscope showed the morphological changes with destructed cell walls of E. coli NCIM 2931 and S. aureus NCIM 5021 cells, when they treated with Ag NPs. The Ag NPs were more effective against S. aureus and E. coli with MIC 128 mu g/ml as compared to P. aeruginosa NCIM 5029 with MIC 256 mu g/ml. Apart from this, the reduction of toxic organic pollutant 4-NP to 4-AP within 20 min reveals the excellent catalytic activity of Ag NPs with rate constant k = 15.69 s(-1). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Ag NPs; Antibacterial; Catalytic activity; Gardenia resinifera; surface plasmon resonance